Progress report towards preventing cow rabies in Mallard, Iran: policies and monitoring measures - Hatami, Hossain; Asgari, Gholam-Reza; Javedan, Gholam-Ali; BarzegarBafroie, Ali-Reza; Bayat, Farzane; Asgari, Hamid Reza; Alipouri sakha, Mino (Researcher Bulletin of Medical Sciences, 2021)
Rabies is one of the most common viral and fetal diseases between humans and animals known as a zoonotic disease. Approximately 99% human rabies deaths occur in developing countries. Health care and follow up programs conducted for all the rabies cases are one of the important priorities for health care system in Iran to prevent the rabies incidence. The purpose of this study is to describe the cow rabies status and the health care programs conducted to the successful elimination of this deadly disease in one of the largest cowsheds in Mallard city in Iran during 2014. After founding the rabies incidence in one of the largest cowsheds in Mallard city in Iran, the crisis committee was held immediately and control measures including isolation, complete quarantine, vaccination of residents, and other sanitation measures were achieved in cooperation with the responsible organizations. During this incidence, 23 calves, cows and heifers were died. By conducting an integrated program and method, the numerous stakeholders contributed to the successful elimination of this fatal disease. In order to control the rabies, it is essential to educate the public on the prevention of the disease, especially in areas where the disease is more prevalence. Therefore, cooperation between the institutions involved in the disease control and planning for emergency disease eradication are essential to prevent the rabies infection among pets, especially livestock